Multidisciplinary rehabilitation for people with Parkinson's disease: a randomised controlled study. Issue 2 (1st February 2003) - Wade, D T; Gage, H; Owen, C; Trend, P; Grossmith, C; Kaye, J
Abstract : Objective: To determine whether a programme of multidisciplinary rehabilitation and group support achieves sustained benefit for people with Parkinson's disease or their carers. Methods: The study was a randomised controlled crossover trial comparing patients and carers who had received rehabilitation four months before assessment with those who had not. Patients were recruited from a neurology clinic, attended a day hospital from home weekly for six weeks using private car or hospital transport, and received group educational activities and individual rehabilitation from a multidisciplinary team. Patients were assessed at entry and at six months using a 25 item self assessment Parkinson's disease disability questionnaire, Euroqol-5d, SF-36, PDQ-39, hospital anxiety and depression scale, and timed stand-walk-sit test. Carers were assessed using the carer strain index and Euroqol-5d. Results: 144 people with Parkinson's disease without severe cognitive losses and able to travel to hospital were registered (seven were duplicate registrations); 94 had assessments at baseline and six months. Repeated measures analysis of variance comparing patients at the 24 week crossover point showed that those receiving rehabilitation had a trend towards better stand-walk-sit score (p = 0.093) and worse general and mental health (p = 0.002, p = 0.019). Carers of treated patients had a trend towards more strain (p = 0.086). Analysis comparing patients before and six months after treatment showed worsening in disability, quality of life, and carer strain. Conclusions: Patients with Parkinson's disease decline significantly over six months, but a short spell of multidisciplinary rehabilitation may improve mobility. Follow up treatments may be needed to maintain any benefit.